Chaunax multilepis sp. nov., a new species of Chaunax (Lophiiformes: Chaunacidae) from the northern Indian Ocean - Ho, Hsuan-Ching; Meleppura, Rajeesh Kumar; Bineesh, K. K. (Zootaxa, 2016)
A new species of Chaunax is described on the basis of eight type and five non-type specimens. This species belongs to the Chaunax abei species group and can be distinguished from congeners in the group by having a continuous tooth patch on the vomer, not divided into two patches, and four or five neuromasts in the lower preopercular series. It can be further separated by the following combination of characters: large green spots on dorsal surface; simple spinules on dorsal surface; 12 pectoral-fin rays; 13–16 neuromasts in pectoral series; 30–37 neuromasts in lateral-line proper; typically four neuromasts on caudal-fin base; typically 7 neuromasts in mandible; typically 12 gill rakers on second gill arch; gill chamber and buccal cavity pale; and peritoneum black.